2020
DOI: 10.18231/2393-9834.2018.0031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of educational status on oral health education program amongst Anganwadi workers in improving oral health of preschool children of Muradnagar block, Ghaziabad-A cross-sectional study

Abstract: Aim: To study effect of educational status of Anganwadi Workers on oral health education program and its impact on improving oral health of preschool children in Muradnagar block, Ghaziabad. Materials and Methods: Study was done amongst 30 Anganwadi Centres of Muradnagar selected by simple random sampling. Sample size was calculated to be 503. Anganwadi Workers were divided into four groups depending on their educational status. Pre tested questionnaire was used to assess baseline knowledge of Anganwadi worker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Their influence extends to shaping the behaviours of their family members, especially the children [21], ultimately impacting their oral health-related behaviours. Further, a strong relationship has been found between maternal OHL, oral healthrelated knowledge, attitude and practices, and children's oral health status [22][23][24]. It is thus imperative to evaluate the OHL of women, as this can facilitate the implementation of effective intervention programmes that will not only enhance women's oral health, but also have a positive impact on their children's oral health.…”
Section: Introductionmentioning
confidence: 99%
“…Their influence extends to shaping the behaviours of their family members, especially the children [21], ultimately impacting their oral health-related behaviours. Further, a strong relationship has been found between maternal OHL, oral healthrelated knowledge, attitude and practices, and children's oral health status [22][23][24]. It is thus imperative to evaluate the OHL of women, as this can facilitate the implementation of effective intervention programmes that will not only enhance women's oral health, but also have a positive impact on their children's oral health.…”
Section: Introductionmentioning
confidence: 99%
“…Their role in the family is essential, and their influence extends to shaping the behaviours of their family members, particularly the children ( Alghamdi et al, 2022 ), thereby impacting children’s oral health-related behaviours. In this regards, studies have demonstrated a strong correlation between maternal OHL and the oral health status of their children ( Dieng et al, 2020 , Sowmya et al, 2021 , Tyagi et al, 2017 ). Intervention programmes in this target group could thus not only improve women’s oral health, but also have a significant positive impact on a children’s oral health.…”
Section: Introductionmentioning
confidence: 99%